Drivers of functional trait-based differentiation in macroinvertebrate communities between lowland and mountainous rivers - Zhang, Yuhang; Zhang, Min; Qu, Xiaodong; Zhang, Haiping; Zhang, Baohang; Wang, Hongtao; Liu, Zhe (Frontiers in Ecology and Evolution, 2025)
Understanding how biological traits and functional diversity of riverine communities respond to environmental factors across different ecoregions is vital for biodiversity conservation and river restoration. This study investigated macroinvertebrates from mountain and lowland rivers in Beijing to compare 33 biological trait categories and six functional diversity indices between these ecoregions. We applied an integrated approach combining environmental variable matrix (R), species community matrix (L), and biological trait matrix (Q) (RLQ) and fourth-corner analyses to link macroinvertebrate traits with hydrological, physical, and chemical factors. Furthermore, generalized linear models (GLMs) were used to compare the responses of traits and functional diversity to multiscale environmental variables and to identify sensitive indicators for ecosystem assessment. Our results showed that 28 of the 33 biological traits differed significantly between the two ecoregions. The mountain ecoregion was characterized by macroinvertebrates with traits such as semivoltine, small and medium size individuals, strong swimming ability, abundant drift, and clinger, shredder, and predator preferred habitats. In contrast, the lowland ecoregion, which experiences greater human impact, was associated with traits such as bi- or multivoltine, large-sized individuals, depositional substrate, warm eurythermal, weak swimming ability, rare drift, and collector–gatherer. All functional diversity indices except Functional Divergence were significantly higher in the mountain ecoregion, demonstrating that environmental stressors in the lowlands substantially reduced functional diversity. The RLQ and fourth-corner analyses confirmed that these biological traits exhibited predictable responses along environmental gradients. The GLM indicated that trait distribution and functional diversity in the two ecoregions were driven by different environmental variables across spatial scales. Hydrological and physical factors explained most of the variations in the mountains, whereas reach-scale chemical factors were the primary drivers of functional diversity loss in the lowlands. This study demonstrates that macroinvertebrate traits and functional diversity serve as effective indicators for river ecosystem health assessment, providing a scientific basis for targeted ecological restoration and sustainable river management.